Durability properties of treated recycled aggregate concrete: Effect of optimized ball mill method - Cakir, Ozgur; Dilbas, Hasan (ELSEVIER SCI LTD, 2021)
In this paper, effects of optimized Ball Mill Method (oBMM) with silica fume (SF) and/or basalt fiber (BF) on durability of untreated recycled aggregate concrete (RAC) and treated recycled aggregate concrete (RAiC) are investigated. 84 concrete series were designed in the experimental program and it is aimed to find the best series objectively depending on experimental results. In the program, many concrete series included natural aggregate (NA), recycled aggregate (RA) and treated RA by oBMM (RAi) and SF, BF SF + BF at various ratios were produced. The physical and the mechanical properties of concretes were determined at the age of 28 days. TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) was considered to select the best concrete series among 84 series. Then, the durability properties of the selected series were determined at the age of 28 days and the test results were compared. According to the test results, it was found that RAi decreased the performance of concrete marginally and oBMM caused a significant improvement compared to RAC. TOPSIS was a useful method to determine the best concrete series and could be used objectively if the weighting coefficients of TOPSIS depended on literature data. It was interesting that the best concrete series determined by TOPSIS were found including 10% SF only for each RA replacement proportions (these are 20%, 40% and 60% by volume) and the best series had satisfactory durability properties in comparison to control concrete. In addition, the durability performance of the best series included up to 60% RAi was generally superior to that of RA. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Recycled aggregate; Ball mill method; Silica fume; TOPSIS; Durability; MECHANICAL-PROPERTIES; COARSE AGGREGATE; COMPRESSIVE STRENGTH; FLY-ASH; STRUCTURAL CONCRETE; PHYSICAL-PROPERTIES; RCA CONCRETE; CLAY BRICK; PERFORMANCE; Construction & Building Technology; Engineering; Materials Science